TRANSLITERASI SEBAGAI PENCIRI MKWU BAHASA INDONESIA DI PERGURUAN TINGGI KEISLAMAN INDONESIA - Mahsusi, Mahsusi; Ying, Luo (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2023)
The obligation to enforce MKWU in teaching Indonesian is also carried out as an effort to use Indonesian at the scientific level. This is done so that disseminating knowledge using the Indonesian language can be implemented immediately. MKWU's Indonesian language teaching must be able to teach students to have scientific writing skills. Subject teachers can apply learning-based models (PBL) to guide students in producing scientific papers. The materials used are Transliteration and EYD. Transliteration material is unique because it is only given to students under the auspices of the Ministry of Religion in Indonesia. This provides an overview of Indonesian courses at Islamic Religious Universities. This study uses a content analysis method with a qualitative approach. The content analyzed is the Indonesian MKWU Semester Learning Plan (RPS). Data sources in this study came from lecturers at MKWU Indonesia at two universities in Jakarta, namely Universitas Islam Negeri Syarif Hidayatullah Jakarta and Universitas Pembangunan Nasional Veteran Jakarta.